National climate strategies show inequalities in global development of carbon dioxide geological storage - Juan Alcalde; Gareth Johnson; Jennifer J. Roberts (Communications Earth & Environment)
Abstract Carbon dioxide geological storage (CGS) is considered critical for limiting global average temperature rise to below 1.5 °C by mitigating fossil industrial emissions and delivering permanent Carbon Dioxide Removals. Here we examine the role of CGS in long-term national emission reduction strategies submitted to the UNFCCC under the Paris Agreement. We find that a third of countries plan to develop CGS for emissions mitigation only, and a third for both emissions mitigation and carbon removals, but no countries plan on CGS for carbon removals alone. Neither the presence or performance of CGS maturity assessments correspond to CGS plans. Climate strategies of high income countries with high historic oil and gas production show firmest commitment to CGS. These countries already have multiple advantages for implementing and benefiting from CGS, which raises inequalities and sensitivities that must be carefully considered when designing carbon market and climate finance policies and frameworks for CGS development.